أثر التّطور اللغوي في فهم القرآن الكريم - . شبايكي, الجمعي; عبيد, مارية (جامعة الوادي - University of Eloued, 2023)
اللغة العربية كائن إجتماعي, لها تأثير كبير وواسع على القرآن الكريم من ناحية الفهم والتفسير, واستنباط الأحكام الشرعية, واستخراج الحكم والفوائد وغيرها, فهي خاضعة للتطور والنمو اللغوي وفق الحضارة الإنسانية, وهذا التطور يتماشى مع النصوص القرآنية, وقد عالجت هذه القضية من جانبين: الأول: بيان حقيقة التطور اللغوي وعوامله, مع بيان آراء العلماء, والثاني: توضيح لأثر التطور اللغوي على فهم القرآن الكريم. وتمكن أهداف البحث على معرفة حقيقة التطور اللغوي في القرآن الكريم, ومدى الاستفادة من هذه الدراسة اللغوية وتطورها في العصر الحديث. The Arabic language is a social being. It has a great and wide influence on the Holy Qur'an in terms of understanding and interpretation, deriving legal rulings, extracting decisions and benefits, and others. It is subject to linguistic development and growth according to human civilization, and this development is consistent with the Quranic texts. The first is an account of the reality of linguistic development and its factors, with an account of the opinions of scholars, and the second is an explanation of the impact of linguistic development on the understanding of the Noble Quran. The objectives of the research were to know the reality of linguistic development in the Holy Quran, and the extent of benefiting from this linguistic study and its development in the modern era.
مقال
Keywords: التطور اللغوي ؛ الفهم؛ النّص القرآني؛ علم الدلالة ؛ اللفظ .